The ״Big Death ״ and the ״Small Death ״ in Shimon Adaf's Aviva-No - Alon, Ketzia (MiKAN, 2021)
At its outset, the essay highlights the prominent place sexuality has in Shimon Adaf's lamentation-poem Aviva-No, and offers an analysis of its images and symbolism. In its latter part the article attempts to track the poets whose influence is evident in the poem, especially those who use a similar mixture of metaphors in their work and with whom Adaf is in dialog. These are mainly the three Israeli poets, Aharon Sabtay, Meir Vizeltir and Avot Yeshurun. The essay details these connections, citing Jewish-French philosopher Emanuel Levinas' comments and analysis on the topic of death as an intellectual-theoretical reference platform.